Movement ecology (BioMed Central, 2013)
"Movement Ecology is an open-access interdisciplinary journal publishing novel insights from empirical and theoretical approaches into the ecology of movement of the whole organism - either animals, plants or microorganisms - as the central theme".
Keywords: ekologie a životní prostředí - jevy; environmentální vědy; Ecological and Environmental Phenomena